Price theory in action ; a book of readings - Watson, Donald Stevenson (Boston : Houghton Mifflin, 1969)
This volume of readings contains illustrations and application of the most significant concepts and techniques of price theory.
Bibliographical footnotes.
osa; 20/12/18
Loans
Keywords: Prices; Price theory